2021
DOI: 10.21931/rb/2021.06.04.8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cultural conditions affecting improved bioactive metabolite production by endophytic fungus Trichoderma harzianum

Abstract: The present study aimed to optimize cultural conditions for optimum bioactive metabolite production by endophytic fungus Trichoderma harzianum, isolated by surface sterilization method from the leaf of the eucalyptus plant. The fungus was identified based on morphological characterization. Fungal metabolites were carried out by ethyl acetate solvent. The antibacterial activity was tested against Escherichia coli (ATCC 25922) and Staphylococcus aureus (NCTC 6571). Various carbon, nitrogen sources, pH, temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The pH, precursors, and incubation time are a few more variables that can affect the formation of bioactive molecules. A large number of microorganisms can produce pH-based secondary metabolites in the range of 5.5 and 8.5 (Thongwai & Kunopakarn, 2007;Hateet et al, 2021). Our study results showed that media supplemented with optimized pH, carbon and nitrogen sources with sodium nitrate showed the maximum antifungal activity by producing secondary metabolites.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…The pH, precursors, and incubation time are a few more variables that can affect the formation of bioactive molecules. A large number of microorganisms can produce pH-based secondary metabolites in the range of 5.5 and 8.5 (Thongwai & Kunopakarn, 2007;Hateet et al, 2021). Our study results showed that media supplemented with optimized pH, carbon and nitrogen sources with sodium nitrate showed the maximum antifungal activity by producing secondary metabolites.…”
Section: Discussionmentioning
confidence: 60%
“…Simple carbohydrates like glucose and dextrose alter metabolic pathways that produce intermediates that produce primary and secondary metabolites in addition to CO 2 , water, and energy. (Hateet et al, 2021). However, initiatives have begun to manipulate dietary components to encourage the microorganism's production of secondary metabolites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations